Malaysia Economic Monitor, June 2019 : Re-energizing the Public Service - World Bank (World Bank, Kuala Lumpur, 2019)
The Malaysia Economic Monitor (MEM) consists of two parts. Part 1 presents a review of recent economic developments and a macroeconomic outlook. Part 2 focuses on a selected special topic that is key to Malaysia’s medium-term development prospects and the achievement of shared prosperity. In this edition, the focus of the special topic is on re-energizing the public service to better enable it to facilitate Malaysia’s future development.